Percutaneous Endoluminal Radiofrequency Ablation of Occluded Biliary Metal Stent in Malignancy Using Monopolar Technique: A Feasibility Study - Rohan, Tomas; Andrasina, Tomas; Matkulcik, Peter; Bernard, Vladan; Valek, Vlastimil (Cardiovascular and interventional radiology, 2022)
PURPOSE: To prove feasibility and safety of percutaneous endoluminal radiofrequency ablation (eRFA) using a monopolar approach in treatment of occluded biliary stent in malignancy. MATERIALS AND METHODS: The study included 11 patients with occluded biliary metal stent that had been implanted due to malignant biliary obstruction. All underwent metal stent recanalization by percutaneous eRFA in monopolar setting. Sixteen eRFA procedures were performed under fluoroscopic guidance with an EndoHPB 8F radiofrequency ablation catheter. The effect of stent recanalization was assessed based upon change from pre- to post-procedural diameter of the patent lumen of the metal stent (Wilcoxon test), primary and secondary stent patency (compared by log-rank test), catheter-free period, and overall survival. Adverse events were evaluated according to Common Terminology Criteria for Adverse Events (CTCEA) 4.0. RESULTS: Recanalization of the metal stent by monopolar radiofrequency ablation was successful in all 11 patients. Diameter of the patent lumen of the stent significantly widened after the eRFA inside the stent (median 2 vs. 7 mm, p = 0.003). Grade 1 complications were observed in one-third of procedures. Median stent patency after recanalization by eRFA was non-inferior to primary metal stent patency (154 vs. 161 days, p = 0.27). Median catheter-free survival and overall survival after stent recanalization were 149 and 210 days, respectively. CONCLUSION: Endoluminal radiofrequency ablation in monopolar setting was shown to be a feasible and safe method for recanalization of occluded biliary metal stents. LEVEL OF EVIDENCE: Level 4, Case Series.
Keywords: radiofrekvenční ablace; Catheter Ablation; Radiofrequency Ablation; Bile Duct Neoplasms; nádory žlučových cest; lidé; retrospektivní studie; studie proveditelnosti; Feasibility Studies; Cholestasis; cholestáza; katetrizační ablace; Retrospective Studies; Stents; Treatment Outcome; výsledek terapie; stenty; Humans